Student’s Perception of Dissecting a Human Cadaver Compared to Usage of 3D Anatomy Virtual Dissection Table to Learn Gross Anatomy - Ali Akmal Naeem, Safwan Tariq Chaudhry, Hira Yaseen (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Limited availability of cadaver and modern discoveries has led to alternate channels to gain anatomy knowledge. Aim: To know the perception of these new sources compared to conventional human dissection. Method: Questionnaire was circulated to for the purpose and results were obtained according to the response. This research is explained in detail according to the result. Result: Majority students were of the view that cadaver dissection is by far the best approach to get the most information of gross anatomy rather than relying on the programmed virtual dissection table. Conclusion: The study strengthen the believe that for gross anatomy human dissection should be performed at the dissection hall meanwhile, the knowledge can be supplemented by the usage of Virtual dissection anatomy table and other modes of information like social media platform. Keywords: Cadaver, Learning, Dissection, Human Anatomy